2020
DOI: 10.1186/s13034-020-0310-3
|View full text |Cite
|
Sign up to set email alerts
|

User participation and shared decision-making in adolescent mental healthcare: a qualitative study of healthcare professionals’ perspectives

Abstract: Background: Most mental health problems occur in adolescence. There is increasing recognition of user participation and shared decision-making in adolescents' mental healthcare. However, research in this field of clinical practice is still sparse. The objective of this study was to explore healthcare professionals' perspectives on user participation, and opportunities for shared decision-making in Child and Adolescent Mental Health Service (CAMHS) inpatient units. Methods: Healthcare professionals at CAMHS inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 44 publications
(81 reference statements)
0
40
0
3
Order By: Relevance
“…We should be aware that the capacity to cope with a child with psychiatric problems is likely to differ between families, and that taking care of children with severe psychopathology and externalizing behaviour can be exhausting, even in the absence of other family problems. Finally, since we found the lack of motivation and compliance with medical treatment to be associated with a compulsory rather than voluntary admission, shared decision-making may be required to increase adolescents' participation in and adherence with psychiatric care [39].…”
Section: Discussionmentioning
confidence: 95%
“…We should be aware that the capacity to cope with a child with psychiatric problems is likely to differ between families, and that taking care of children with severe psychopathology and externalizing behaviour can be exhausting, even in the absence of other family problems. Finally, since we found the lack of motivation and compliance with medical treatment to be associated with a compulsory rather than voluntary admission, shared decision-making may be required to increase adolescents' participation in and adherence with psychiatric care [39].…”
Section: Discussionmentioning
confidence: 95%
“…The client needs to want to be involved in SDM and be trained how to engage in it, and the professional should be aware of SDM techniques and should place the therapeutic alliance with the patient at the center of the interaction, offering clear information and actively listening to the client's viewpoints. In support of this, it has been found that establishing effective relationships based on a personcentered and user participation model are more important in decision-making than following an established pathway with little consultation (30). Additionally, the three-talk model of SDM (9) highlights the need for active listening between the parties leading to discussion of possible options for the service user to make when facing a decision.…”
Section: Discussionmentioning
confidence: 99%
“…Trust between patients and therapists has been described in previous studies ( 18 , 28 , 29 ). Routines for adolescents to participate in treatment meetings and selecting their treatment team should, according to our results, be established to facilitate shared decision-making ( 20 ). The significance of information is also highlighted in previous research ( 18 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results also show a link between shared decision-making and workplace culture. Teamwork, positive clinicians, leadership support, and a culture that promotes user participation are key elements in the implementation of shared decision-making ( 20 , 28 , 31 ). Earlier research support an assertion that shared decision-making mobilizes adolescents to engage in therapy thus making it more likely that they will continue with treatment ( 8 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation